Uang Panai’ Sebagai Salah Satu Syarat Perkawinan Pada Suku Bugis Makassar - Ruslan, Dyah Auliah Rachma (BAMETI Customary Law Review, 2023)
Uang Panai' is an amount of money that must be given by the prospective husband to the family of the prospective wife which is used as expenses for the wedding reception. The tradition of giving Uang Panai' is one of the concerns of many people outside the Makassar Bugis tribe because it is not uncommon for the bride's family to ask for fantastic amounts of Uang Panai. This sometimes burdens the prospective groom and his family, causing the prospective groom to withdraw and cancel his intention to marry the prospective bride. This is what makes the writer feel interested in discussing Uang Panai' as a condition for marriage in the Makassar Bugis tribe. The research method used is normative legal research. The main subject of the study is law which is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior. Results of the Research is uang Panai' is not a legal condition for marriage, but only an additional condition that is customary for the Bugis people. So that if the bridegroom does not give Uang Panai', the marriage can still take place and remains valid religiously and legally